Poverty, quality of life and psychological wellbeing in adults with congenital heart disease in Chile - López Barreda, Rodrigo (PLoS One, 2020)
The objective of this study was to assess the quality of life and psychological wellbeing of adults with congenital heart disease (CHD) in Chile, and to identify other associated factors. The study enrolled 68 patients aged between 18 and 72 (median 29), 35 being females. They completed a questionnaire, which included a quality of life assessment tool (the Medical Outcome Study 36-Item Short Form Health Survey), a number of psychological scales (the General Health Questionnaire, the Basic Psychological Needs Scales and the Beck Hopelessness Scale), a socioeconomic survey, and some clinical data. CHD patients reported worse scores in those scales assessing physical dimensions of quality of life (physical function (70.5), physical role functioning (64), vitality (65.3)), and general quality of life (58.6), than in emotional or social dimensions. Female gender was associated with lower scores in physical function (59.12 versus 82.66; p<0.01) and physical role functioning (53.68 versus 75; p<0.05); poverty was associated with worse results in physical function (61.92 versus 82.96; p<0.01), role physical (53.21 versus 79.63; p<0.01), vitality (60.89 versus 71.67; p<0.05), social role functioning (70.19 versus 82.87; p<0.05) and bodily pain (65.77 versus 81.2; p<0.05). Furthermore, we found that psychological scales had an association with quality of life, but clinical variables did not show significant correlations to any dimension. Poverty has an impact on the quality of life of CHD patients. This population only has a decrease in the quality of life physical dimensions, suggesting that quality of life depends on many different factors.